General practitioners' beliefs about the clinical utility of complementary and alternative medicine. Issue 3 (3rd June 2014) - Jarvis, Aron; Perry, Rachel; Smith, Debbie; Terry, Rohini; Peters, Sarah
<x content-type="archive" xml:space="preserve">Abstract</x> Aim To investigate GPs' beliefs about complementary and alternative medicine (CAM) and its role in clinical practice. Background Despite the prevalence of CAM in the United Kingdom, little is known about GPs beliefs regarding these alternative approaches to patient management and how they view it in relation to their clinical conduct and practice. Method A qualitative study conducted on 19 GPs recruited from the North West of England. Semi-structured telephone interviews were analysed using an inductive thematic analysis. Results Three themes emerged from the data: limited evidence base, patient demand and concerns over regulation. Conclusion Despite recognising the limited evidence base of CAM, GPs continue to see a role for it within clinical practice. This is not necessarily led by patient demand that is highly related to affluence. However, GPs raised concerns over the regulation of CAM practitioners and CAM therapies.